Resistance training rejuvenates the mitochondrial methylome in aged human skeletal muscle. Issue 9 (23rd August 2021) - Ruple, Bradley A.; Godwin, Joshua S.; Mesquita, Paulo H. C.; Osburn, Shelby C.; Vann, Christopher G.; Lamb, Donald A.; Sexton, Casey L.; Candow, Darren G.; Forbes, Scott C.; Frugé, Andrew D.; Kavazis, Andreas N.; Young, Kaelin C.; et al.
Abstract: Resistance training (RT) dynamically alters the skeletal muscle nuclear DNA methylome. However, no study has examined if RT affects the mitochondrial DNA (mtDNA) methylome. Herein, ten older, Caucasian untrained males (65 ± 7 y.o.) performed six weeks of full‐body RT (twice weekly). Body composition and knee extensor torque were assessed prior to and 72 h following the last RT session. Vastus lateralis (VL) biopsies were also obtained. VL DNA was subjected to reduced representation bisulfite sequencing providing excellent coverage across the ~16‐kilobase mtDNA methylome (254 CpG sites). Biochemical assays were also performed, and older male data were compared to younger trained males (22 ± 2 y.o., n  = 7, n  = 6 Caucasian & n  = 1 African American). RT increased whole‐body lean tissue mass ( p  = .017), VL thickness ( p  = .012), and knee extensor torque ( p  = .029) in older males. RT also affected the mtDNA methylome, as 63% (159/254) of the CpG sites demonstrated reduced methylation ( p  < .05). Several mtDNA sites presented a more "youthful" signature in older males after RT in comparison to younger males. The 1.12 kilobase mtDNA D‐loop/control region, which regulates replication and transcription, possessed enriched hypomethylation in older males following RT. Enhanced expression of mitochondrial H‐ and L‐strand genes and complex III/IV protein levels were also observed ( p  < .05). While limited to a shorter‐term intervention, this is the first evidence showing that RT alters the mtDNA methylome in skeletal muscle. Observed methylome alterations may enhance mitochondrial transcription, and RT evokes mitochondrial methylome profiles to mimic younger men. The significance of these findings relative to broader RT‐induced epigenetic changes needs to be elucidated.